PERAN BIDAN DALAM PELAKSANAAN PERMENKES NOMOR 631/MENKES/ PER/III/2011 SEBAGAIMANA TELAH DIUBAH DENGAN PERMENKES NOMOR 2562/MENKES/PER/XII/2011 TENTANG PETUNJUK TEKNIS JAMINAN PERSALINAN (Studi Kasus Pelayanan Kebidanan Di RSUD dr. H. Soewondo Kendal - . Sariyati; Endang Wahyati Y; C. Tjahjono Kuntjoro (Universitas Katolik Soegijapranata Semarang, 2016)
The role of midwives in service delivery assurance in dr. H. Soewondo Kendal based on Permenkes No. 2562/MENKES /PER/XII/2011 on Technical Guidelines for Labor Warranty. The aim is to implement the appropriate authority midwifery services, with the ultimate goal of reducing the MMR (Maternal Mortality Rate) and IMR (Infant Mortality Rate). If viewed from Permenkes 1464/Menkes /Per/X/2010 number of licenses and the implementation of midwifery practice, it is not really appropriate authority for the role of the midwife in the hospital to service delivery is a delivery service assurance of advanced midwives in hospitals. The scope of service includes pregnant women, maternity (risti), childbirth, newborns, family planning and treatment of complications in obstetrics. So based on the authority role of the midwife in the hospital should not be for the scope of services for maternity delivery guarantee (risti) and treatment of complications in obstetrics